2018
DOI: 10.1016/j.ensm.2018.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Binding MoSe2 with carbon constrained in carbonous nanosphere towards high-capacity and ultrafast Li/Na-ion storage

Abstract: Mostly reported MoSe2 suffered from easily stacking problem, volume expansion and relative low capacity. From the experience of Li/Na-Se batteries, the exfoliated and encapsulated MoSe2 inside carbon nanospheres with C-O-Mo bonds and large layer distance (0.89 nm) are successfully constructed. This unique effective structure has C-O-Mo bonding allowing high conductivity across the Se-O insulation layer and promoting its reversible conversion. The first-principles calculations demonstrated that the frontier mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
114
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 206 publications
(122 citation statements)
references
References 66 publications
2
114
0
Order By: Relevance
“…According to the EIS equivalent circuit (the inset of Figure g), the R ct value of H‐WS 2 @NC (49 Ω) is much lower than that of S‐WS 2 @NC (113 Ω) and bare WS 2 (374 Ω), confirming the remarkably enhanced kinetics of electronic transportation provided by the architecture of H‐WS 2 @NC electrode. Furthermore, the diffusion kinetics of Na + ion in the electrode material can be determined by the Z′–ω −1/2 (ω = 2πf) curves in the low‐frequency region and diffusion coefficient ( D Na , cm 2 s −1 ) can be estimated according to the following formulae Z=Re+Rct+σω1/2 D = R2 T2/2A2n4F4C2σ2…”
Section: Resultsmentioning
confidence: 99%
“…According to the EIS equivalent circuit (the inset of Figure g), the R ct value of H‐WS 2 @NC (49 Ω) is much lower than that of S‐WS 2 @NC (113 Ω) and bare WS 2 (374 Ω), confirming the remarkably enhanced kinetics of electronic transportation provided by the architecture of H‐WS 2 @NC electrode. Furthermore, the diffusion kinetics of Na + ion in the electrode material can be determined by the Z′–ω −1/2 (ω = 2πf) curves in the low‐frequency region and diffusion coefficient ( D Na , cm 2 s −1 ) can be estimated according to the following formulae Z=Re+Rct+σω1/2 D = R2 T2/2A2n4F4C2σ2…”
Section: Resultsmentioning
confidence: 99%
“…The full survey spectrum ( Figure S3, Supporting Information) clearly showed that the Mo, Se, C signals and some traces of O 2 delineated the high purity of the product. [38] Besides, a weak peak at 230.4 eV is also observed in the high-resolution spectrum of Mo, which is attributed to Se 3s. [38] Besides, a weak peak at 230.4 eV is also observed in the high-resolution spectrum of Mo, which is attributed to Se 3s.…”
mentioning
confidence: 91%
“…[34][35][36][37][38] Recently,s everal research groups have attempted to maximize the sodium-ion storage properties of anodesb yi ntegrating the two strategiesm entioned above. [18][19][20][21][22][23][24][25][26][27][28][39][40][41][42][43] This could significantly improve the structural and physicalp ropertieso f electrode materials to achieve high electrochemical performance. For example, Tu and co-workersp repared 3D carbon-MoSe 2 -reducedg raphene oxide composites through a facile hydrothermalm ethod.…”
Section: Introductionmentioning
confidence: 99%